Analytical Modeling of Threshold Voltage and Drain-Induced-Barrier- Lowering Variations Due to Gate Length Fluctuation in Nanometer MOSFETs - Weifeng, Lu; Guangyi, Wang; Mi, Lin; Lingling, Sun (Recent Advances in Electrical & Electronic Engineering, 2017)
Background: In state-of-the-art nanometer metal-oxide-semiconductor-field-effecttransistors (MOSFETs), threshold voltage (VT) and drain-induced-barrier-lowering (DIBL) variations are regarded as significant challenges in circuit analysis, design and characterization. Method: This paper proposes the improved analytical models to correctly describe VT and DIBL variations due to random gate length fluctuation employing the propagation of variation (POV) methodology. Result: The presented models are validated that they can accurately capture VT and DIBL’s statistical characteristics through Monte Carlo simulations for MOSFET devices with 22nm process technology. Furthermore, our models and simulations both revealed that VT and DIBL variations will increase dramatically with gate length shrinking for nanometer MOSFETs. Conclusion: The proposed statistical modeling approach provides a useful pathway for processvariation- aware circuit design.
Keywords: threshold voltage